An Assessment of Linezolid Utilization in Selected Canadian Provinces - Sandra Walker; Linda Dresser; Debbie Becker; Alissa Scalera (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Linezolid is approved for the treatment of designated infections caused by methicillin-resistant and -susceptible Staphylococcus aureus and vancomycin-resistant Enterococcus faecium.